Ebstein’s Anomaly: Anesthetic Management at shahid Gangalal National Heart Centre - Upreti, Murari Raj; Pokharel, Jeju Nath (Nepalese Heart Journal, 2017)
During the last eight years, 34% of the cases have been congenital; out of which only 0.7% have been Ebstein’s Anomaly. In the literature they have mentioned that the male and female ratio is 1:1, but there are more female than male in our series, 15:3.